Once upon a time in Mexico [videorecording (DVD)] - Rodriguez, Robert, 1968-; Banderas, Antonio; Hayek, Salma, 1966-; Depp, Johnny (Columbia TriStar Home Entertainment, 2004)
The saga of El Mariachi contunues when a corrupt CIA agent forces him out of hiding to help sabotage an assassination attempt on the president of Mexico by an evil cartel kingpin. El Mariachi has his own reason for helping - he is doing it for revenge.